Review: Salmonella Dublin in dairy cattle - Velasquez-Munoz, Ana; Castro-Vargas, Rafael; Cullens-Nobis, Faith M.; Mani, Rinosh; Abuelo, Angel (Frontiers in Veterinary Science, 2024)
Salmonella enterica serovar Dublin (S. Dublin) is a bacterium host-adapted to cattle with increasing prevalence in dairy facilities. It can severely affect cattle health, producing high morbidity and mortality in young calves and reducing the performance of mature animals. S. Dublin is difficult to control and eradicate from herds, as it can be shed from clinically normal animals. In addition, S. Dublin is a zoonotic bacterium that can be lethal for humans and pose a risk for human and animal health due to its multi-drug resistant characteristics. This review provides an overview of S. Dublin as a pathogen in dairy facilities, the risk factors associated with infection, and current strategies for preventing and controlling this disease. Furthermore, current gaps in knowledge are also discussed.